Principles of solar engineering - Goswami, D. Yogi (Taylor & Francis, 2000)
This second edition of Principles of Solar Engineering covers the latest developments in a broad range of topics of interest to students and professionals interested in solar energy applications. With the scientific fundamentals included, the book covers important areas such as heating and cooling, passive solar applications, detoxification and biomass energy conversion. This comprehensive textbook provides examples of methods of solar engineering from around the world and includes examples, solutions and data applicable to international solar energy issues. A solutions manual is available to qualified instructors.